THE RISK MANAGEMENT OF SCHOOL OPERATIONAL ASSISTANCE (BOS) FUNDS IN BONE BOLANGO REGENCY - Andriean Andjar; Asna Aneta; Ismet Sulila; Yanti Aneta (Adisam Publisher, 2026)
This study aims to analyze the risk management of School Operational Assistance (BOS) funds in Bone Bolango Regency from the perspectives of public administration and good governance. The study was motivated by the persistence of various problems in the management of BOS funds, such as delays in fund disbursement, weak supervision, limited human resource capacity, and the suboptimal implementation of transparency and accountability in school financial administration. This study employed a qualitative approach with a descriptive method. Data collection techniques were conducted through observation, in-depth interviews, and documentation. Data analysis utilized an interactive model consisting of data reduction, data presentation, and conclusion drawing. The findings reveal that risk management in the governance of BOS funds in Bone Bolango Regency has not yet operated optimally. Based on the Berg Risk Management Model approach, the identified risks include goal setting, risk identification, risk analysis, risk assessment, risk treatment selection, as well as monitoring and evaluation. The implementation of good governance principles such as transparency, accountability, effectiveness, and community participation still requires strengthening. This study recommends improving the capacity of BOS fund managers, strengthening internal supervision, digitalizing financial management systems, and enhancing coordination among educational stakeholders in order to establish effective and accountable governance of educational operational funding.